2021
DOI: 10.3390/w13091177
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Modeling of Climate Variability Impact on River Runoff

Abstract: The hypothesis of this study was one of existence of spatially organized links between the time series of river runoff and climate variability indices, describing the oscillations in the atmosphere–ocean system: ENSO (El Niño–Southern Oscillation), PDO (Pacific Decadal Oscillation), AMO (Atlantic Multidecadal Oscillation), and NAO (North Atlantic Oscillation). The global river flow reconstructions (ERA-20-CM-R) for 18 study areas on six continents and climate variability indices for the period 1901–2010 were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…A trained model must perform well on data available during the training data process as well as test data [22]. A split data technique is commonly utilized, in which a larger subset of existing records is used for learning models and a smaller sample for testing models [23]. Usually, these are referred to as training and test sets, respectively.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…A trained model must perform well on data available during the training data process as well as test data [22]. A split data technique is commonly utilized, in which a larger subset of existing records is used for learning models and a smaller sample for testing models [23]. Usually, these are referred to as training and test sets, respectively.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…The results showed that local observations and climate indices were best at longer lead times. Norel et al [36] In this sense, the data resources used in this work consisted of the HPP list (Table 1), the historical series of streamflow obtained in [37], available in the period 1931-2020, and the historical series of climate indices available in [15], totaling twenty-six indices (Table 2) in distinct periods.…”
Section: Methodsmentioning
confidence: 99%
“…ENSO: El Niño -Southern Oscillation; NAO: North Atlantic Oscillation; AMO: Atlantic Multi-decadal Oscillation; PDO: Pacific Decadal Oscillation), cf. Kundzewicz et al, 2019Kundzewicz et al, , 2020Norel et al, 2021).…”
Section: Changes In Intense Precipitation and High Flood Hazard -Observations And Projectionsmentioning
confidence: 99%